2019
DOI: 10.1021/acsami.9b10338
|View full text |Cite
|
Sign up to set email alerts
|

Optical Device Based on a Nanopillar Array by the Pattern Transfer of an Anodic Aluminum Oxide Membrane

Abstract: A simple and convenient nanofabrication method is proposed to achieve nanopillar arrays by the pattern transfer of an anodic aluminum oxide membrane, profiting from the rapid and efficient preparation process and regular hexagonal lattice patterns of the anodic aluminum oxide template. The taper angle of the nanopillar is affected by the distribution of the vapor particles during the deposition process, which is highly dependent on the material and deposition power. Based on this method, a novel scheme employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Yang et al demonstrated how a similar nanopillar array based on aluminum oxides can be constructed with a low-cost method by pattern transfer and anodization and still hold superior optical properties in the visible range compared with an untextured metasurface. 201 In another metal oxide texturing application, Danilov et al developed plasmonic-based nanostructures on copper oxide films by ablative and nonablative one-photon absorption of femtosecond laser radiation. 194 The optical transmission spectra showed sharp peaks at approximately 590 nm for the irradiated samples that were not present for thin films prepared without nanostructuring, demonstrating the potential of this fabrication technique for refractive-indexbased sensing applications.…”
Section: Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al demonstrated how a similar nanopillar array based on aluminum oxides can be constructed with a low-cost method by pattern transfer and anodization and still hold superior optical properties in the visible range compared with an untextured metasurface. 201 In another metal oxide texturing application, Danilov et al developed plasmonic-based nanostructures on copper oxide films by ablative and nonablative one-photon absorption of femtosecond laser radiation. 194 The optical transmission spectra showed sharp peaks at approximately 590 nm for the irradiated samples that were not present for thin films prepared without nanostructuring, demonstrating the potential of this fabrication technique for refractive-indexbased sensing applications.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…Yang et al demonstrated how a similar nanopillar array based on aluminum oxides can be constructed with a low-cost method by pattern transfer and anodization and still hold superior optical properties in the visible range compared with an untextured metasurface . In another metal oxide texturing application, Danilov et al developed plasmonic-based nanostructures on copper oxide films by ablative and nonablative one-photon absorption of femtosecond laser radiation .…”
Section: Surface Texturingmentioning
confidence: 99%
“…Eqn (13) indicates, in addition to the aluminium oxalate in the AAO membranes, the reflectivity of the structure with the nanochannel arrays contributes to the absorbance, which has also influenced the organic-inorganic hybrid self-pigmenting, the concentration of aluminium oxalate can be given by…”
Section: Composition and Structure Dependence Of The Organicinorganic...mentioning
confidence: 99%
“…Self-ordered anodic aluminium oxide (AAO) membranes with hexagonally packed nanochannel arrays have become promising candidates for versatile applications including nanofluidic transport, 1 filtration, 2 separation, 3 ionic current rectification, 4 sensors, 5,6 and biodetection, 7 as well as the construction of various nanostructures (such as nanorods, 8,9 nanowires, 10,11 nanoparticles 12 and nanopillars 13 ), and the design of optical devices, 13 biosensor 14,15 and energy conversion devices 16 through the AAO template-based assembly approach, where the composition and the structural characteristics of the AAO membranes play key roles in their functional applications. Interestingly, the compositions of the AAO membranes are not completely composed of aluminium oxide; partially acid anion-contaminated species have been inevitably incorporated into the membrane during the formation of the nanochannels, 17,18 and the alumina composition in the barrier layer produces a different pattern of surrounding hexagonal walls.…”
Section: Introductionmentioning
confidence: 99%
“…Nano- and microscaled surface modifications and functionalizations have enormous potential in a wide variety of applications, e.g., solar cells, decoration, super-hydrophobicity, biosensing, biomimetic, electronics, and photonic applications . Nanopatterning allows for anisotropic physical properties like polarization-dependent optical responses or by enhancing inherent optical and electronic material properties and is suitable for appliances of high technological interest such as LEDs, , transistors, or solar cells. , Lithographic and multibeam techniques , are state of the art for advanced surface finishing, but they are time-consuming and/or costly. The alternative laser-induced patterning method presented in this work is fast, suitable for large areas, spatioselective, and requires only a nanosecond laser and a quarter-wave plate.…”
mentioning
confidence: 99%